The Role of Customer Loyalty in Mediating Corporate Social Responsibility and the Company's Financial Performance - Nurul Aini; Rudi Harianto; Nina Rizki Rahayu (LPPM of NAROTAMA UNIVERSITY, 2021)
ABSTRACK Purpose: This study aims to examine and analyze the mediating effect of customer loyalty on the influence of Corporate Social Responsibility toward financial performance.Design/methodology/approach: This research is quantitative study using secondary data taken from Indonesia Stock Exchange 2014-2017. The data analysis technique used is the WarpPLS 6.0 program which is carried out in two testing stages; the direct and indirect impacts of Corporate Social Responsibility variables on financial performance.Findings: The result indicates that customer loyalty variable partially mediates the effect of Corporate Social Responsibility on financial performance. It means customer loyalty does not fully mediate the effect of Corporate Social Responsibility on financial performance.Research limitation: CSR measurement uses an index that calculates CSR based on the quantity not the quality of implementation. Practical implications: This researchprovides an illustration to the company that the implementation of proper and serious CSR has an impact on growing the company's financial performance.Originality/value: This research is a development from previous research by adding consumer loyalty as a mediating variable.Paper type: This is categorized as a research paper. Keywords: customer loyalty, Corporate Social Responsibility, financial performance